Potensi Umbi Porang (Amorphophallus oncophyllus Prain) Sebagai Pakan Ayam Broiler - Zendrato, Desti Prestasi; Tafsin, Ma’ruf; Hanafi, Nevy Diana; Sadeli, Achmad; Julianti, Elisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Porang tuber (Amorphophallus oncophyllus Prain) contains glucomannan as a prebiotic source which can be used as animal feed to improve the performance of broiler chickens. The aim of the study was to determine the potential of porang, to analyze the nutritional content and its use as a feed ingredient for broiler chicken rations. The research was conducted at Rumah Mbacang Pancur Batu Village, from April-June 2022. This data was obtained from the results of proximate analysis at the Laboratory of Small Ruminant Instrument Standard Testing Workshop, Sei Putih, Galang. Data is processed manually and presented descriptively. The preparation of the ratio formulation consists of P0 (0% porang flour), P1 (5% porang flour), P2 (10% porang flour) and P3 (15% porang flour). The parameters studied: water content, crude protein (CP), crude fiber (CF), crude fat (EE) and NNFE. The results showed that the results of the proximate analysis on porang flour: moisture 12.92%, ash 8.22%, CP 4.19%, CF 4.79%, EE 0.62%, NNFE 69.26%. The water content and CP met the requirements according to SNI 7939: 2013, namely quality I. The conclusion from the results of formulation preparation was obtained a good composition of the formulation with nutritional content, starter phase: CP 20.08-20.59%, ME 2948.00-2985.08 Kcal/kg, CF 4.11-4.15%, EE 4.25-4.63%, Ca 0.78-0.79%, P 0.61-0.62% and finisher phase: CP 18.34-19.07 %, ME 3017.49-3050.65 Kcal/kg, CF 3.79-3.83%, EE 4.19-4.59%, Ca 0.56-0.68%, P 0.53-0.56%.